Geographical indications and health-conscious behaviors among nursing students: A mixed methods study - Esin Kavuran; Erkan Denk (PLoS ONE, 2026)
This study was conducted using a Sequential Explanatory Design, in which the quantitative phase was carried out first, followed by a qualitative phase to examine the influence of nursing students’ attitudes toward purchasing Geographical Indication (GI)–certified products and their mindful eating practices on their healthy eating attitudes. The study population consisted of 1.385 nursing students enrolled in a faculty of nursing. The quantitative component included 392 students who met the inclusion criteria, while the qualitative component comprised 15 students. For data collection, the quantitative phase employed a sociodemographic data form, the Healthy Eating Attitude Scale (HEAS), the Mindful Eating Scale (MES), and the Attitude Scale for Purchasing GI-Certified Products (ASP-GICP). In the qualitative phase, data were collected using a Semi-Structured Interview Form. Quantitative findings showed that younger students (17–25 years) and females had significantly higher scores in GI product attitudes and mindful eating (p < 0.01). Students with greater knowledge of GI products and those with healthier personal eating habits demonstrated more positive healthy eating attitudes. Structural Equation Modeling revealed that attitudes toward purchasing GI products (S.P.T = 0.32, t = 3.10, R² = 0.10) and mindful eating (S.P.T = 0.29, t = 2.90, R² = 0.08) significantly predicted healthier eating attitudes. Furthermore, mindful eating exhibited a significant moderating effect, strengthening the positive impact of GI product attitudes on healthy eating attitudes (β = 0.27, t = 3.10, p = 0.003). Qualitative interviews highlighted the influence of societal and familial norms on students’ perceptions of GI products, while cost and limited accessibility emerged as key barriers. The study concludes that integrating GI product awareness and mindful eating practices into nursing education may strengthen students’ health-conscious behaviors and support their development as future health professionals.